Spatial Diversity Impact in Mobile Quantisation Mapping for Cognitive Radio Networks - Arief Marwanto; Sharifah Yusof; M Satria (IAES Indonesia Section, 2019)
Mobile environment especially spatial diversity in spectrum exchange information in cognitive radio networks is an interesting topic for further investigation. Most of the cognitive radio researchers does not consider the spatial diversity of sensing nodes. However, the mobility of the SNs within PU’s coverage area is heavily influencing the detection performance on local observation of energy signals. The movement of the SNs creates spatial diversity in the observation of the PU’s signal. Due to the movement, spatial distance, velocity, Doppler Effect and geo-location information, the signals condition would fluctuate during the sensing process. Spatial diversity also reduces the average received signal strength and must be compensated by detection signal method which appropriate with the signal conditions. Therefore, it is need to find a comprehensive solution to overcome the effects of spatial diversity. Moreover, this research could give a clearly analysis in spectrum exchange information regarding detection performance for cognitive radio networks. Finally, the cooperation overhead due to spatial diversity effects in master node station could reduce and increased the detection performance of PU’s spectrum hole channels.